Oxford progressive english book 8 - Redford, rachel (Oxford University Press; Karachi, 2019)
Oxford Progressive English Book 8 is a comprehensive English language coursebook that develops reading, writing, listening, and speaking skills through a range of engaging texts, activities, and language exercises tailored for Grade 7 students.